Conservative treatment of diffuse infiltrating retinoblastoma: optical coherence tomography-assisted diagnosis and follow-up in three consecutive cases. Issue 6 (26th July 2018) - Stathopoulos, Christina; Moulin, Alexandre; Gaillard, Marie-Claire; Beck-Popovic, Maja; Puccinelli, Francesco; Munier, Francis L
Abstract : Background/aims: To report conservative therapy in diffuse infiltrating retinoblastoma (DIR) and describe specific optic coherence tomography (OCT) features of the tumour. Methods: Retrospective review of all DIR cases treated conservatively between 1998 and 2012. Results: Three patients (three eyes) were included, cases 1 and 3 with previous enucleation of the contralateral eye and case 2 with unilateral retinoblastoma referred after prior pars plana vitrectomy with silicone oil. Mean age at diagnosis was 7 years (range 14 months–14 years). Globe and vision preservation (Snellen visual acuity of 12.5/10) was achieved in case 3 with a recurrence-free follow-up of 33 months after first-line thermotherapy followed by salvage intra-arterial chemotherapy (IAC) plus focal treatments. Cases 1 and 2 were enucleated for progressive disease, case 1 after first-line intravenous chemotherapy (IVC) consolidated by focal therapies and salvage treatments given over 8 years of partial remission and case 2 after IAC, brachytherapy and intracameral chemotherapy. Neither showed any high-risk histopathological features, and no adjuvant chemotherapy was necessary. Both patients are alive without metastasis (mean follow-up of >10 years). Pathognomonic features of the tumour were revealed by OCT in all cases, showing infiltration of the ganglion cell layer and horizontal growth over the inner plexiform layer. Complete restoration of the retinal microanatomy was documented after retraction of the tumour following IVC in case 2 and IAC in case 3. Conclusion: This is the first report of successful conservative management in DIR. OCT enabled diagnosis, delimitation of the tumour margins and monitoring of the treatment response in this context.